Women's Decisions to Stay in or Leave an Abusive Relationship: Results From a Longitudinal Study in Bolivia. (November 2018) - Heim, Eva; Ajzen, Icek; Schmidt, Peter; Seddig, Daniel
This study examined Bolivian women's decisions to stay with or leave their violent partners. The theory of planned behavior (TPB) was used as the theoretical framework. One hundred thirty-four women were assessed 3 times over 6 months. The TPB constructs were measured at T1 and T2; relationship status was assessed at T3. At T2, attitudes about staying and leaving predicted the intention to leave. Intention to leave at T2 but not at T1 predicted relationship status at T3. These results suggest that the decision to leave was consolidated between T1 and T2, and attitudes toward staying were most relevant to this decision.